1952
DOI: 10.1017/s0080456800009224
|View full text |Cite
|
Sign up to set email alerts
|

I.—On the Developmental Processes in Mammary Glands and other Epidermal Structures

Abstract: Synopsis:The early development of the mammary glands and of hair follicles in the mouse and the rabbit has been investigated by means of mitotic counts, by histochemical methods and by cultivation in vitro. In the first stage of the formation of both types of rudiment a thickening of the epidermis appears as a consequence of an aggregation of cells, not of a local elevation of the mitotic rate. During this stage alkaline phosphatase is absent from the cells and the content of ribose-nucleic acid reduced. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…On the other hand, this fact is in keeping with the in vitro studies of the mouse breast model, in which hormones such as insulin, prolactin and aldosterone, unlike estrogen and progesterone, seem to be heavily involved in early growth [9,10]. On the other hand, low cell proliferation was also demonstrated in the mouse model, in which the mitotic index of the fetal breast gland turned out to be lower than that of the surrounding epidermis [6]. The puberal breast showed high ER and PR expression, which is probably the consequence of the intense hormonal stimulation to which the breast is exposed in this phase of growth.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, this fact is in keeping with the in vitro studies of the mouse breast model, in which hormones such as insulin, prolactin and aldosterone, unlike estrogen and progesterone, seem to be heavily involved in early growth [9,10]. On the other hand, low cell proliferation was also demonstrated in the mouse model, in which the mitotic index of the fetal breast gland turned out to be lower than that of the surrounding epidermis [6]. The puberal breast showed high ER and PR expression, which is probably the consequence of the intense hormonal stimulation to which the breast is exposed in this phase of growth.…”
Section: Discussionsupporting
confidence: 73%
“…We also demonstrate that Nrg3 regulates epithelial progenitor accretion without increasing epithelial mitosis. The limited epithelial proliferation detected cannot account for the observed increases in mammary primordial size that occur between E10.5 and E13.5 and influx of cells from the adjacent surface epithelium accounts for most increases in epithelial cell numbers within the nascent organ [15][16][17]. Our results indicate Nrg3 signals mediate the distribution of epithelial progenitor cells along the ventral thoracic flank at the time that they are thought to be locally migrating to form the MP.…”
Section: Alterations In Epithelial Progenitor Cell Distributions Inmentioning
confidence: 81%
“…As a result, much remains to be understood regarding the cellular and molecular mechanisms by which the initial MP is developed from the simple epithelium. It has been clearly established that a very low level of cell proliferation is detected within the mammary primordial epithelium during the initial stages of organ formation from E11 through E14 stages [15,16]. Previous studies have concluded that early mammary morphogenesis is primarily mediated via localized cell movements [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the signals involved in this inductive event are unknown, the actual formation of the mammary ridge and bud does not appear to involve increased local epithelial proliferation insofar as the formation of the thickened mammary ridge proceeds too rapidly to be ex plained by cell proliferation [Balinsky, 1950: Propper, 1970, and the mitotic index of the early mammary anlagen is in fact lower than the surrounding epidermis [Balinsky, 1950]. Indeed, it has been postulated that the mesenchyme-induced formation of the mammary bud involves cell migration and change in cell shape [Balinsky.…”
Section: Discussionmentioning
confidence: 99%